2010
DOI: 10.5380/rf.v40i2.17830
|View full text |Cite
|
Sign up to set email alerts
|

EFEITO DA GRAMATURA SOBRE A RESISTÊNCIA AO CISALHAMENTO DA LINHA DE COLA DE DUAS MADEIRAS TROPICAIS: SERU (Allantoma lineata) E MARUPÁ (Simarouba amara)

Abstract: Este trabalho teve como objetivo principal estudar a influência da gramatura do adesivo resorcinol-formaldeído na união de peças de madeira, visando à produção de madeira laminada colada (MLC) de duas espécies, seru (Allantoma lineata) e marupá (Simarouba amara), e da mistura entre elas. Foram realizados testes de cisalhamento na linha de cola conforme a NBR 7190 (1997), bem como foi calculada a percentagem de falha na madeira para as duas espécies e para dois tipos de mistura entre elas nas gramaturas 200, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…The coincidence between the greater occurrence of C. gestroi and the greater loss of mass of the P. elliottii stakes could be related to wood density (0.40 g cm -3 ), which is the lowest amongst the forest species evaluated (0.57 g cm -3 para S. morototoni, 0.60 g cm -3 for A. lineata and 1.04 g cm -3 for M. huberi) (Tomazello et al, 1983;IPT, 2017a, b;Santos & Del Menezzi, 2010), while MDF presented a density of around 0.50 g cm -3 (Maloney, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The coincidence between the greater occurrence of C. gestroi and the greater loss of mass of the P. elliottii stakes could be related to wood density (0.40 g cm -3 ), which is the lowest amongst the forest species evaluated (0.57 g cm -3 para S. morototoni, 0.60 g cm -3 for A. lineata and 1.04 g cm -3 for M. huberi) (Tomazello et al, 1983;IPT, 2017a, b;Santos & Del Menezzi, 2010), while MDF presented a density of around 0.50 g cm -3 (Maloney, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…When studying the effect of the weight on the shear strength in the glue line of two tropical woods, Santos and Del Menezzi (2010) found that the adhesive of resorcinol-formaldehyde at 200 g/m 2 weight was not effective in bonding the evaluated species. Teles et al (2010) studied the effect of weight on the quality of glued joints, and found that the efficiency and quality of the adhesion of the resorcinolformaldehyde adhesive was influenced by weight and showed an increase in joint strength bonded with the increment of the weight of the adhesive, where the greatest resistance was obtained with the weight of 300 g/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…A colagem é uma etapa fundamental para o melhor aproveitamento do material madeira, tanto no setor moveleiro quanto na construção civil (FRIHART, 2011;LIMA et al, 2008;DEL MENEZZI, 2010). No entanto, os trabalhos existentes na literatura tratam da avaliação da interação entre madeira e adesivo para compensados pela variação da gramatura (ALBINO et al, 2011;ALMEIDA et al, 2004), sendo que há uma escassez de estudos dessa natureza para painéis particulados (KHOSRAVI et al, 2011).…”
Section: Introductionunclassified